The Effect Of Different Caries Removal Methods On The Surface Hardness and Micro-tensile Bond Strength - Selin Nacak Doğuş; Nurcan Özakar (Atatürk University, 2024)
Objective: This study aims to evaluate the effects of five different caries removal methods on caries removal effectiveness according to microhardness and micro tensile bond strength values. Materials: In this study, for the microhardness test, micro-tensile bond strength test (n = 10) SEM analysis (n = 2), and a total of 72 human molar teeth were used. Caries lesions were removed with conventional (steel bur, ceramic bur, polymer bur) methods, chemomechanical method (Brix-3000), and fluorescence-aided caries excavation method (Siroinspect). Then, teeth were sectioned longitudinally through the cavity center and were subjected to the microhardness test, micro tensile test, and SEM atomic analysis. Statistical analyses were performed using one-way ANOVA and Duncan post-hoc tests. Results: A statistically significant difference was found between all caries removal methods and measurement levels at certain distances from the cavity floor (0, 25, 50, 75 μm) (p